4,6-O-Phenylethylidene Acetal Protected D-Glucosamine Carbamate-Based Gelators and Their Applications for Multi-Component Gels - Pooja Sharma; Guijun Wang (Gels, 2022)
The self-assembly of carbohydrate-based low molecular weight gelators has led to useful advanced soft materials. The interactions of the gelators with various cations and anions are important in creating novel molecular architectures and expanding the scope of the small molecular gelators. In this study, a series of thirteen new C-2 carbamates of the 4,6-O-phenylethylidene acetal-protected D-glucosamine derivatives has been synthesized and characterized. These compounds are rationally designed from a common sugar template. All carbamates synthesized were found to be efficient gelators and three compounds are also hydrogelators. The resulting gels were characterized using optical microscopy, atomic force microscopy, and rheology. The gelation mechanisms were further elucidated using 1H NMR spectroscopy at different temperatures. The isopropyl carbamate hydrogelator 7 formed hydrogels at 0.2 wt% and also formed gels with several tetra alkyl ammonium salts, and showed effectiveness in the creation of gel electrolytes. The formation of metallogels using earth-abundant metal ions such as copper, nickel, iron, zinc, as well as silver and lead salts was evaluated for a few gelators. Using chemiluminescence spectroscopy, the metal–organic xerogels showed enzyme-like properties and enhanced luminescence for luminol. In addition, we also studied the applications of several gels for drug immobilizations and the gels showed sustained release of naproxen from the gel matrices. This robust sugar carbamate-derived gelator system can be used as the scaffold for the design of other functional materials with various types of applications.